2009
DOI: 10.1634/stemcells.2008-0710
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF-Brg1 Regulates Self-Renewal and Occupies Core Pluripotency-Related Genes in Embryonic Stem Cells

Abstract: The SWI/SNF-Brg1 chromatin remodeling protein plays critical roles in cell-cycle control and differentiation through regulation of gene expression. Loss of Brg1 in mice results in early embryonic lethality, and recent studies have implicated a role for Brg1 in somatic stem cell self-renewal and differentiation. However, little is known about Brg1 function in preimplantation embryos and embryonic stem (ES) cells. Here we report that Brg1 is required for ES cell self-renewal and pluripotency. RNA interference-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
224
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(250 citation statements)
references
References 59 publications
(83 reference statements)
26
224
0
Order By: Relevance
“…The requirement for Brg in ES cell maintenance and in blastocysts was reported recently by Knott and coworkers (39), confirming earlier results with gene deletion and studies reported here. In addition, we show that Brg acts in the context of a specialized complex, esBAF.…”
Section: Discussionsupporting
confidence: 93%
“…The requirement for Brg in ES cell maintenance and in blastocysts was reported recently by Knott and coworkers (39), confirming earlier results with gene deletion and studies reported here. In addition, we show that Brg acts in the context of a specialized complex, esBAF.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with the research of Kidder et al (2009), who showed that RNA interferencemediated knockdown of BRG1 in embryonic stem cells resulted in a loss of pluripotency and self-renewal.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that Ezh2 is required for GC formation and the SWI/SNF complex synergistically regulates several genes together with the Ezh2-PRC2 complex (36)(37)(38)(39). MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40).…”
Section: Discussionmentioning
confidence: 99%